Parent-school-community relationship: a comparative study of highly effective schools and schools with low effectiveness in Andalusia (UCL Press, 2024)
When studying an educational system, the relationship between school and parents is one of its most important components. The literature shows that highly effective schools demonstrate good parent-teacher relationships, while schools with low effectiveness are generally characterised by a lack of good parent-school linkage. The purpose of the research carried out in this article was to identify the differences between parent-school relationships in highly effective and less effective primary schools in the autonomous community of Andalusia. Twenty-five interviews with members of management teams from both types of schools were analysed in order to understand the existing school reality. The results obtained show that parental involvement, parent-school communication, the perceived needs of the parents, the parent-teacher association, the relationships with entities of the educational community and parental complaints about the school are all factors that contribute to differentiate parent-school relationships between highly effective schools and schools with low effectiveness. The conclusions reached reveal that highly effective school management teams perceive greater involvement of parents and better parent-teacher association functioning. However, the people in the schools with low effectiveness highlight the complaints they receive from parents and the needs they present.